PROSES PRODUKSI AMBENG STOOL HIJAU SAGE BERBAHAN DASAR PLASTIK JENIS HDPE (High-density polyethylene) DI ROBRIES (PT. Siklus Karya Global) - M. Daigo Gusnanda; F. Alqap, A. Sofwan; Hestiawan, Hendri (Rekayasa Mekanika: Jurnal Ilmiah Teknik Mesin, 2025)
The manufacturing process is an activity or production process that transforms raw materials into finished goods. To accelerate production, the manufacturing process utilizes modern equipment such as machines and implements structured programs to carry out production. The purpose of this internship is to understand the procedures for making the sage green Hambeng Stool, determine the optimal plastic melting time, and identify the factors influencing product defects at Robries. Raw materials are modified through manufacturing processes to form the necessary components. To produce the desired product, several stages must be followed. In its production, the manufacturing process requires machining stages. The manufacturing process begins with designing the product and determining the material specifications for the product. The methods used in this research include literature review, observation, and interviews. This is because the desired product cannot be produced through a single machining process. The production process at ROBRIES complies with the standard operating procedures (SOP), starting with material selection, material melting, material sanding, and finishing.